A Sephardi Sea : Jewish Memories across the Modern Mediterranean - Miccoli, Dario (Book collections on Project MUSE., 2022)
"A Sephardi Sea tells the story of Jews from the southern shore of the Mediterranean who, between the late 1940s and the mid-1960s, migrated from their country of birth for Europe, Israel, and beyond. It is a story that explores their contrasting memories of and feelings for a Sephardi Jewish world in North Africa and Egypt that is lost forever but whose echoes many still hear. Many of the migrants were already familiar with and spoke the language of their new countries. Why, then, was the act of leaving so painful and why, more than fifty years afterward, is its memory still so tangible? Dario Miccoli examines how the memories of a bygone Sephardi Mediterranean world became preserved in three national contexts-Israel, France, and Italy-where the Jews of the Middle East and North Africa and their descendants migrated and nowadays live. A Sephardi Sea explores how practices of memory- and heritage-making has filled an identity vacuum in the three countries and helps the Jews from North Africa and Egypt to define their Jewishness in Europe and Israel today but also reinforce their connection to a vanished world now remembered with nostalgia, affection, and sadness"--